1994
DOI: 10.1007/bf00126274
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of reagents for peptide bond formation: Crystal and molecular structures of HBTU and HATU

Abstract: X-ray structure determinations of HBTU and HATU, well-known reagents for peptide bond formation, show that the solid-state structures of these compounds differ markedly from those commonly presented in the literature. The solid-state structures are isomers of the N,N,N',N'-tetramethyluronium salt formulation commonly written for HBTU and HATU. HBTU and HATU, obtained either directly from synthesis or from CH3CN solution, crystallize as the guanidinium N-oxide isomers. Both compounds crystallize in nearly ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 16 publications
8
74
0
1
Order By: Relevance
“…Method A: A mixture of protected iminodiacetic acid (0.25 mmol), HBTU [8] (0.5 mmol) and DIEA (1 mmol) was stirred at 0 ~ for 3-5 rain in DMF (2 ml) and then added to a solution of an amino acid ester or amino acid amide hydrochloride (0.5 mmol) and DIEA (0.5 mmol) in 2 ml of DMF at 0 ~ The reaction mixture was stirred at 0 ~ for 1 h and overnight at rt. The reaction mixture was diluted with 75 ml of ethyl acetate, and the mixture was washed with 1 N HC1 (2 x 10 ml), satd NaHCO3 (2 x 10 ml), and saturated NaC1 (2 x 10 ml).…”
Section: General Methods For Activation and Coupling For The Synthesismentioning
confidence: 99%
“…Method A: A mixture of protected iminodiacetic acid (0.25 mmol), HBTU [8] (0.5 mmol) and DIEA (1 mmol) was stirred at 0 ~ for 3-5 rain in DMF (2 ml) and then added to a solution of an amino acid ester or amino acid amide hydrochloride (0.5 mmol) and DIEA (0.5 mmol) in 2 ml of DMF at 0 ~ The reaction mixture was stirred at 0 ~ for 1 h and overnight at rt. The reaction mixture was diluted with 75 ml of ethyl acetate, and the mixture was washed with 1 N HC1 (2 x 10 ml), satd NaHCO3 (2 x 10 ml), and saturated NaC1 (2 x 10 ml).…”
Section: General Methods For Activation and Coupling For The Synthesismentioning
confidence: 99%
“…Synthetic scheme for preparing TOMBU (17) and COMBU (18). Carpino et al [28] reported that HBTU (4) and HATU (5) exist in the N-form (guanidinium salt) instead of the O-form (uronium salt) and that the two forms can easily be distinguished by means of 13 C-NMR spectroscopy. The carbocationic carbon of the N-form appears at 151-152 ppm while that of the O-form appears at 161-162 ppm [29,30].…”
Section: Preparation Of Tombu and Combumentioning
confidence: 99%
“…They crystallize as aminium salts, as the guanidinium N-oxide isomers. 57 In solution the two forms could co-exist, since either could react with a carboxyl group to give the activated ester intermediate. Figure 28).…”
Section: Aminium Saltsmentioning
confidence: 99%